Molecular Evaluation of Traditional Chicken Farm-Associated Bioaerosols for Methicillin-Resistant Staphylococcus aureus Shedding - Chi-Wei Tao; Jung-Sheng Chen; Bing-Mu Hsu; Suprokash Koner; Tung-Che Hung; Han-Ming Wu; Jagat Rathod (MDPI AG, 2021)
The outbreak of airborne pathogens, such as methicillin-resistant Staphylococcus aureus (MRSA) through bioaerosol, and their molecular characterization around domestic poultry farming areas, was not completely understood. This imposes risk of a MRSA-associated health threat for the relevant livestock food production units. To address this issue, the present study investigated the role of bioaerosol in transmitting MRSA strains in poultry house settings by combining molecular typing, phylogenetic classification, antibiotic susceptibility, and virulence gene distribution patterns. The present study highlights that all 18 bioaerosol and stool samples collected were MRSA positive, with a unique set of virulence factors. Out of 57 isolated MRSA isolates, 68.4% and 19.3% consisted of SCCmec I and IV elements, respectively, which are commonly linked with hospital-acquired and livestock-associated MRSA strains. It is worth noting that the exfoliative toxin eta and etb genes were carried by 100% and 70.2% of all isolates, respectively. Only 17.5% of strains showed the presence of enterotoxin entC. These MRSA isolates were resistant to chloramphenicol (C), ciprofloxacin (CIP), clindamycin (DA), erythromycin (E), and tetracycline (T), signifying their multi-drug resistance traits. A cluster of phylogenetic analysis described that 80.7% and 15.8% of total isolates belonged to Staphylococcus aureus protein A (spa) type t002 and t548. Whereas 3.5% were reflected as a new spa type. Additionally, as per the chi-squared test score value, these two spa types (t002 and t548) have a distribution correlation with HA-MRSA and LA-MRSA in all the samples (p < 0.005, chi-squared test; degree of freedom = 1). Ultimately, this study highlights the prevalence of MRSA colonization in the conventional poultry farm environment, showing the risk of bioaerosol transmission, which needs epidemiological attention and prevention strategies.